Analyzing Competitive advantage indicators among telecom operators in Algeria: A comparative study - Boudiaf, Ilyes; Djadli, Samir; Chorfi, Moncef (Dirassat Journal Economic Issue, 2022)
This study aims to measure the differences of competitive advantage indicators between telecom operators in Algeria. On the basis of three approaches; the descriptive, inductive and comparative approach, we tried to answer the main question and carry out the empirical study. For data collection, we use the questionnaire of sample of 153 employees and some short interviews with managers, as well as some reports about telecoms market published by ARPCE. To test the hypothesis, we use the one-way ANOVA test. Finally, we have found that there are no significant differences between telecom operators about competitive advantage indicators, according to the studied sample.